Nicotinamide ameliorates energy deficiency and improves retinal function in Cav‐1‐/‐ mice. Issue 3 (30th December 2020) - Tang, Yizhen; Fang, Wangyi; Xiao, Zebin; Song, Maomao; Zhuang, Dongli; Han, Binze; Wu, Jihong; Sun, Xinghuai
Abstract: Caveolin‐1(Cav‐1) is involved in lipid metabolism and energy homeostasis, which is important for the energetically demanding retina. Although retinal function deficits were noted in Cav‐1 knockout (Cav‐1 ‐/‐ ) mice, the underlying causes remain largely unknown. Here, we investigate if the disruption in energy homeostasis presents a potential mechanism for retinal function deficits in Cav‐1 ‐/‐ retina and if it can be ameliorated by nicotinamide (NAM). In this study, NAM was administrated orally for 2 weeks in Cav‐1 ‐/‐ mice before experiments. Oxidative lipidomics was conducted to detect the oxylipin changes, the retinal energy flux was measured by seahorse assay, and the retinal function was assessed by electroretinogram (ERG). Cav‐1 deficiency induced the dysregulation of oxidative lipidomics and reduction in energy consumption/production in the retina by decreasing Na + /K + ‐ATPase, oxidative phosphorylation CII, cytochrome c, and oxygen consumption rate (OCR). A decrease in Sirt1 was also detected. Therapeutic administration of NAM significantly increased Sirt1 expression and improved energy deficiency by increasing Na + /K + ‐ATPase, cytochrome c, and OCR. The dysregulation of oxidative lipidomics was partially recovered, and the retinal function was improved as assessed by ERG compared to Cav‐1 ‐/‐ mice. Our study demonstrated the dysregulation of oxidative lipidomics in Cav‐1 ‐/‐ retina and established a link between energy deficiency and retinal function deficits in Cav‐1 ‐/‐ mice. Administration of NAM ameliorated energy deficiency, increased the expression of Sirt1, and improved retinal function, which presents a potential therapeutic strategy for Cav‐1 deficiency‐induced retinal function deficits. Abstract : The present study established a link between energy deficiency and impaired retinal function in Caveolin‐1 knockout (Cav‐1 ‐/‐ ) mice. Cav‐1 deficiency, instead of directly altering retinal structure, leads to a dysregulation in lipid oxidation and energy deficiency in the retina. Nicotinamide (NAM) treatment recovered the expression of sirtuin 1 (Sirt1), benefited energy flux, and promoted retinal function recovery, indicating that targeting NAM could improve the Cav‐1 deficiency‐induced impaired retinal function.